PENGARUH PROJECT-BASED LEARNING (PJBL) TERHADAP KETERAMPILAN SISWA PADA PEMAHAMAN BERITA DI SMP NEGERI 2 SIBOLANGIT TAHUN PEMBELAJARAN 2025/2026 - Br Ginting, Yemima; Losten Tamba; Candra Ronitua Gultom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the significant effect of implementing the Project- Based Learning (PjBL) model on the news comprehension skills of eighth-grade students at SMP Negeri 2 Sibolangit in the 2025/2026 academic year. The research employed a post-test-only control group design with a sample of 59 students divided into two groups: 29 students in the control class and 30 students in the experimental class. The research instrument was a test administered to 59 students and validated by experts. The normality test showed that the control class obtained a statistic value of 0.166 with a significance (p-value) of 0.364, while the experimental class obtained a statistic value of 0.127 with a significance of 0.200, indicating that both significance values were above the 0.05 threshold and thus normally distributed. The homogeneity test using Levene’s Test showed a Levene Statistic value of 3.695 with a significance (Sig.) of 0.060 based on the mean approach. Since the significance value was greater than 0.05, it can be concluded that the variances between the experimental and control classes were homogeneous. The t-test result showed t = 11.798 (df = 57) with Sig. 0.000 < 0.05, indicating a significant difference between the experimental class (mean = 88.66) and the control class (mean = 66.62). The mean difference of 22.03 (95% CI: 18.18–25.89) indicates that the learning applied in the experimental class significantly improved students’ learning outcomes.